Strategi Pemulihan Citra Merek (Brand Image Recovery) Aqua Pasca Krisis Isu “Sumur Bor” di Media Sosial - Djakaria, Mohamad Rinaldi; Sahabi, Ansar (Politeknik Kebangsaan, 2025)
This study examines Aqua’s brand image recovery strategy following the “bore well” crisis circulating on social media, which significantly influenced public perceptions of the company’s transparency and integrity. The issue triggered a high level of attributed responsibility, requiring the company to implement theoretically grounded crisis communication strategies. This research aims to evaluate the effectiveness of Aqua’s recovery measures, including official clarifications, the disclosure of technical information regarding water sources, and the reinforcement of compliance with regulatory requirements. The study employs a descriptive qualitative approach through the analysis of documents, corporate statements, and public responses on social media. The findings indicate that Aqua adopted a rebuild strategy through corrective actions and enhanced transparency; however, the effectiveness remains limited due to gaps between corporate messaging and public expectations for independent verification. The analysis further reveals that brand image recovery in the digital era requires the integration of transparent information, external validation, and responsive two-way communication to restore trust. This study underscores that the success of brand image recovery depends on message consistency, accountability, and the company’s ability to adapt to rapidly evolving public discourse.